CML Developing Three Years after Therapy Completion in a Child with Ph(−) Pre-B-ALL - S. Hosseini; G. H. Bahoush; P. Vousogh; Sh. Ansari; Kh. Arjmandi; M. Sabzechian (Case Reports in Hematology)
We report a girl with a history of Ph(−) pre-B-ALL and three years of disease-free survival admitting to our hospital for regular end of treatment checkup with an increased white blood cell count which in follow-up studies and molecular detection of BCR-ABL (p210) fusions gene had been diagnosed as a Ph(+) typical CML. The upcoming question in this case scenario is whether developed CML is a secondary leukemia due to previous ALL chemotherapy or just a relapse case of primary leukemia.